IDENTIFICATION 'AND ANALYSIS OF CONCEPTS PERCEIVED AS DIFFICULT TO TEACH BY SCIENCE TEACHERS - Atadoga, Moses M. (Sokoto Educational Review, 2011)
This paper focused on the identification and analysis of concepts perceived by Basic science teachers as difficult to teach. The study adopted a survey design. The population of this study comprised all the junior school (JS) teachers in all the 78 universal Basic Education (UBE) schools in Dekina Local Government Area of Kogi state. The subjects included 118 JS teachers that teach Basic science _ from 60 schools in Dekina Local Area of Kogi state. The instrument used for data collection was a questionnaire prepared to fry the researcher. The data were interpreted and analyzed using mean(X), standard deviation (SD) and correlation. The result of the study showed that Basic Science teachers found physical science concepts difficult to teach while most of the biological and health science concepts were easy to teach. Some of the reasons are given for the difficulty include the inability of the teachers to understand the curriculum, inadequate instructional materials and teachers’ course of studies or qualifications. Recommendations made included the employment of competent and qualified teachers and regular training and retraining of Basic science teachers.